Genetic and Non-Genetic Factors Influencing Fatty Acid Composition of Dairy Milk: A Review - Chaudhary, Rajni; Rai, Sweta; Sailo, Lalrengpuii; Farooq, Uiase Bin; Singh, Akansha; Naha, Binoy Chandra; Kumar, Amit (Indian Journal of Animal Nutrition, 2017)
Milk is a natural, complete and balanced food as it is a rich source of fat, protein, vitamins and minerals. On the same time, many surveys revealed that diet plays an important role as a risk factor for chronic diseases in humans. Prospective cohort studies have identified association between dietary fat type (like saturated fatty acid) and cardiovascular diseases. The concentration of milk fatty acids in ‘model’ milk fat for human health should contain